2000
DOI: 10.3133/ds57
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic framework of Lower and Upper Cretaceous rocks in central and eastern Montana

Abstract: Large accumulations of biogenic gas are known to exist in shallow (<3,000 ft deep) Cretaceous reservoirs of the Northern Great Plains (mainly Montana) and southeastern Alberta and southwestern Saskatchewan, Canada. The 1995 USGS National oil and gas assessment made a mean estimate of 1.15-1.18 x 10 12 m 3 (41-42 trillion cubic ft) of potential additions to reserves of continuous-type (unconventional) gas in Cretaceous shallow biogenic gas plays of northern and central Montana (Rice and Spencer, 1995). About 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…al., 2006;Feldmann et al, 2012), although the vertical thickness at the discovery site of MOR 3072 was not measured. This westward-thinning tongue of marine shale disconformably overlies the Judith River Formation and is conformably overlain by the Fox Hills Sandstone in Montana (Feldmann et al, 1977;Condon, 2000) and the Eastend Formation in Canada (He et al, 2005). The Bearpaw Shale grades eastward into the Pierre Shale (Condon, 2000) and the outcrop similarity between the Bearpaw and Pierre shales makes these two units physically synonymous in the upper midcontinent of North America (Tourtelot, 1962;Feldmann et al, 2012).…”
Section: Geologic Settingmentioning
confidence: 95%
“…al., 2006;Feldmann et al, 2012), although the vertical thickness at the discovery site of MOR 3072 was not measured. This westward-thinning tongue of marine shale disconformably overlies the Judith River Formation and is conformably overlain by the Fox Hills Sandstone in Montana (Feldmann et al, 1977;Condon, 2000) and the Eastend Formation in Canada (He et al, 2005). The Bearpaw Shale grades eastward into the Pierre Shale (Condon, 2000) and the outcrop similarity between the Bearpaw and Pierre shales makes these two units physically synonymous in the upper midcontinent of North America (Tourtelot, 1962;Feldmann et al, 2012).…”
Section: Geologic Settingmentioning
confidence: 95%
“…In this study, the Arrow Creek and Clay Spur bentonites were identified by their stratigraphic positions at the base of the Mowry Shale (Condon, 2000) and within the base of the Belle Fourche Shale (Morath, 2007), respectively. When the Arrow Creek bentonite was not present, the Albian-Cenomanian boundary was chosen using palynological data from Scott et al (1998) (for the Bounds core) and regional trends of depletion in oxygen isotopic signatures from paleosol sphaerosiderites in the Kenyon and Bounds cores (based on the boundary pick described in White et al, 2005).…”
Section: Marker Horizonsmentioning
confidence: 99%
“…For example, the parasequences present at the base of the Northeastern Wyoming Composite section (parasequences 1-9) are not observed in the Bounds and Kenyon cores. The early Cenomanian strata in northeastern Wyoming was deposited in a wholly marine environment (Condon, 2000) in the axial portion of the KWIS (Kauffman and Caldwell, 1993), whereas the coeval strata in the Bounds and Kenyon cores were deposited in a fluvial/deltaic setting (MacFarlane et al, 1991) near the eastern paleoshoreline of the KWIS (Hamilton, 1994). Therefore, less accommodation space was available in the Kansas, precluding the deposition of parasequences 1-9 (i.e., nondeposition and/or erosion).…”
Section: Ma = Million Years (Age); Ma = Million Years (Duration); Ky mentioning
confidence: 99%
“…There are a number of published isopach and structural maps of the Pierre Shale and its correlative unit, the Bearpaw, for this region (Shurr, 1977;Carlson, 1982;Smith, 1999;Condon, 2000); data from Condon (2000) for eastern Montana were used to generate GIS data for the Bearpaw (Figure 2-20). Inventory of Shale Formations in the US, Including Geologic, Geochemical, Hydrological, Mechanical, and Thermal Characteristics 24 September, 2014…”
Section: Williston Basinmentioning
confidence: 99%